Do Foreign Institutional Investors impact Compliance with CSR Expenditure Regulation? Evidence from India - Geeta Singh (Copernican Journal of Finance & Accounting)
The paper examines the impact of foreign institutional investors’ (FIIs) equity holding on the non compliance with the mandatory CSR expenditure of the Indian firms from 2016 to 2020. Using a sample of 1423 listed firms, we employ OLS and Logit regression models to establish that an increase in the FIIs reduces the extent of non compliance with mandatory CSR expenditure as well as the likelihood of such non-compliance. Findings of the study support the monitoring role of the FIIs to reduce information asymmetry and agency problem. Further, we provide the channel for the negative relation between FIIs and non-compliance as FIIs’ capability to reduce free cash flows of the firms. Given the presence of business groups in India, we conduct an additional analysis for the relation between FIIs and non-compliance with CSR regulation in business groups, and report a more pronounced negative relation in the member firms. Our study can provide insights for the policy makers as well as investors to understand the importance of FIIs in compliance with the regulation and in impacting the firms’ reputation.